1991
DOI: 10.1128/jvi.65.1.313-319.1991
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally introduced defective endogenous proviruses are highly expressed in chickens

Abstract: We have previously described the experimental introduction of recombinant subgroup A avian leukosis viruses (ALV) with Rous-associated virus 0 long terminal repeats into the germ line of line 0 chickens and the generation of 23 transgenic lines. Two of these transgenic lines, alv6 and alvll, do not produce infectious virus. Both of these lines contain defective proviruses but do express the gag and/or env protein. We have measured viral RNA expression in tissues derived from alv6, alvll, and the parental line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The presence of infectious ASLV in chickens was determined by assaying the 8-week serum samples on two different cell lines with different ASLV envelope subgroup susceptibilities: DF-1 cells (C/E) which supports the replication of ASLV(A), ASLV(B), and ASLV(C); and line alv 6 CEF (C/A) [38] which supports ASLV(B) and ASLV(C) replication. Serum samples (100 μL) were added to the cells and the cells were incubated for 9 days in media (5% serum) to allow ASLV to spread.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of infectious ASLV in chickens was determined by assaying the 8-week serum samples on two different cell lines with different ASLV envelope subgroup susceptibilities: DF-1 cells (C/E) which supports the replication of ASLV(A), ASLV(B), and ASLV(C); and line alv 6 CEF (C/A) [38] which supports ASLV(B) and ASLV(C) replication. Serum samples (100 μL) were added to the cells and the cells were incubated for 9 days in media (5% serum) to allow ASLV to spread.…”
Section: Methodsmentioning
confidence: 99%
“… a Serum samples were cultured on DF-1 cells (C/E) that support the replication of ASLV(A), ASLV(B), and ASLV(C); and on line alv 6 CEFs (C/A) [38] that support ASLV(B) and ASLV(C) but not ASLV(A) replication. ELISA assays detecting ASLV capsid protein (CA) in serum were performed 8 weeks after virus challenge.…”
Section: Figurementioning
confidence: 99%
“…Cells and animals that express retroviral envelope glycoproteins, due to a naturally occurring or genetically engineered endogenous virus, are highly resistant to retroviruses using the same receptor and have less virus-associated pathogenesis. Based on the example of the resistance of chicken lines that express endogenous subgroup E envelope glycoproteins to ALV(E) infection (38), Crittenden and colleagues demonstrated that insertion of the ALV(A) envelope gene into the germ line of chickens and its subsequent expression provided resistance to infection by ALV(A) strains by receptor interference (12,18,41,42). However, the general utility of receptor interference as an antiviral strategy may be limited for retroviruses that express cytotoxic envelope glycoproteins (17,21).…”
mentioning
confidence: 99%
“…Most ALV-K isolates have endogenous LTR that shows considerable homology with that of endogenous virus ALV-E (Li et al, 2016;Zhao et al, 2018;Lv et al, 2019). The genomic difference between ALV-K and ALV-E was centered in SU encoded by gp85 (Figure 1) because ALV-E does not infect DF-1 (Federspiel et al, 1991); hence, the difference The supernatant was collected and diluted in gradient to determine the virus titers. Three independent experiments were performed, and data are shown as mean ± SD in triplicate from a representative experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The DF-1 cell line used in this study is a continuous fibroblastic cell line derived from line 0 CEFs, which is not susceptible to endogenous virus ALV-E (Federspiel et al, 1991) but to exogenous virus ALV-K. Endogenous virus ALV-E ev-1 (GenBank: AY013303.1) and exogenous virus ALV-K GDFX0602 (GenBank: KP686143.1) show considerable homology (LTR: 98.5%; gp37: 98.9%; gp85: 87.9%) (Zhao et al, 2018), and the regions with considerable differences are primarily located in hr1 and hr2. Unlike ALV-K, ALV-E shares the Tvb-encoded tumor necrosis factor receptor with ALV-B/D as a receptor that is encoded by three alleles: tvb s1 , tvb s3 , and tvb st (Adkins et al, 1997).…”
Section: Introductionmentioning
confidence: 99%